Complex vertical layering and mixing of aerosols over the eastern Mediterranean: Active and passive remote sensing at the Cyprus University of Technology - Mamouri, Rodanthi-Elisavet; Nisantzi, Argyro; Hadjimitsis, Diofantos G.; Ansmann, Albert; Schwarz, Anja; Basart, Sara; Baldasano, José María (My University, 2013)
Aerosols can have a complicated influence on climate conditions, directly as well as indirectly via cloud formation. The southeastern Mediterranean region can be characterized as a cross road of aerosols originating from European, Asian and African continents. Complex vertical aerosol distributions are frequently detected over Cyprus by means of active remote sensing. Observations of such complex aerosol layering and comparison of the measurements with aerosol products of regional and global atmospheric transport models are required to improve our understanding of life cycles of aerosol mixtures and their impact on climate as well as on satellite remote sensing products. In this study, a case of an intense desert dust outbreak from Syria and Saudi Arabia towards the eastern Mediterranean in September 2011 is presented. The observations used in this study were performed with a 532-nm polarization Lidar and a sun/sky AERONET photometer operated at 8 channels from 340 to 1640 nm wavelength. Both instruments belong to remote sensing station of the Cyprus Technical University at Limassol, Cyprus (34°N, 33°E). The lofted dust plume was doped with air masses that crossed sources of biomass burning smoke and anthropogenic pollution. In addition, the shallow marine boundary layer over the Mediterranean Sea and over Limassol became mixed with the anthropogenic haze by sea breeze circulations. The case study demonstrates the potential of combined lidar/photometer observations to deliver detailed vertically resolved information of the aerosol characteristics in terms of particle optical and microphysical properties, separately for the spherical particle fraction as well as for the non-spherical aerosol mode.
Keywords: Aerosol mixtures; Arabian dust; Mediterranean; Polarization lidar; Remote sensing